APPLICATION OF LEARNING MATHEMATICS USING WEB BASED LEARNING METHOD - M. Ichsan Alfajri; Yusli Yenni (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
Mathematics is one branch of science that we have learned from an early age. Mathematics is the science of quantity, structure, space, and change. Mathematicians find patterns from rigorous conclusions drawn from consistent axioms and definitions, propose new conjectures, and construct truth. We often encounter a learning approach that becomes a problem in the real world as a context for learning by thinking more critically and skillfully in problem-solving and knowledge and concepts from the material to be learned. The success of learning can be seen from the results of learning. Therefore, learning methods related to technology are indispensable for practical activities with the object of study cannot be separated from theoretical learning. Learning theory makes us bored compared to the practice done directly in front of the computer with existing technology at the moment. One such technology is Web-Based Learning (WBL). Using the Web-Based Learning (WBL) method is expected to help develop its capabilities